Polygala tenuifolia and Acorus tatarinowii in the treatment of Alzheimer’s disease: a systematic review and meta-analysis - Zhang, Yuchen; Tian, Jinzhou; Ni, Jingnian; Wei, Mingqing; Li, Ting; Shi, Jing (Frontiers in Pharmacology, 2024)
Objective To evaluate the clinical efficacy and safety of the combination of PT and AT in the treatment of AD. Methods We systematically searched and screened randomized controlled trials (RCTs) of pairing PT and AT for the treatment of AD patients in eight databases with a search deadline of June 26, 2023. Authors, year of publication, title, and basic information such as subject characteristics (age, sex, race), course of disease, control interventions, dose, and treatment duration were extracted from the screened studies. Primary outcomes assessed included Mini-mental state examination (MMSE), Activities of daily living (ADL), and AD assessment scale-cognitive subscale (ADAS-cog), while secondary outcomes included efficiency and adverse events. The quality of the included studies was assessed using the Cochrane Risk of Bias Tool. The mean difference with 95% confidence intervals (MD [95% CI]) and risk ratio (RR) was selected as the effect size and the data were analyzed and evaluated using RevMan 5.4 and Stata 16. Results A total of sixteen eligible and relevant studies involving 1103 AD participants were included. The combination of PT and AT plus conventional drugs was superior to single conventional drugs in MMSE, ADL and ADAS-cog scores. The combination of PT and AT plus conventional drugs had a significantly more favorable benefit in clinical effectiveness. Adverse events were not increased with the combination of PT and AT plus conventional drugs compared to conventional drugs. The experimental group treated with the combination of PT and AT alone for AD was comparable in MMSE, ADL, and ADAS-cog scores compared with the control group treated with single conventional drugs. Conclusion Compared to single conventional drugs, the combination of PT and AT may be used as an alternative therapy to improve global cognition and functioning in AD, and the combination of PT and AT as adjunctive therapy appears to produce a better therapeutic response to AD in terms of efficacy without increasing the risk of adverse events. However, the very low to low quality of available evidence limits confidence in the findings.